Fractional order PI controller design for non-monotonic phase systems - Verma S.K.; Yadav S.; Nagar S.K. (My University, 2025)
In this paper, a fractional order proportional-integral (FOPI) controller is proposed for controlling the non-monotonic decreasing phase DC-buck regulator system. The parameters of FOPI controller are optimized by Nelder's-Mead (NM) method. The FOPI controller provides fast closed-loop performance as well as improves the robust properties of the system in time and frequency domain. The controller preserves the monotonic phase between the desired bandwidth and improves the characteristic performance of the system. The proposed method is validated by comparing the time domain as well as frequency domain characteristics with the integer order proportional-integral (IOPI) controllers tuned using various techniques. © 2016, IFAC (International Federation of Automatic Control) Hosting by Elsevier Ltd. All rights reserved.